Factors associated with the quality of care in the adult population affiliated to Social Security: the Peruvian case - Soto-Becerra, Percy (2020)
Objetive: To identify factors associated with perceived quality of care in the adult population affiliated with Social Security Health (EsSalud) Material and methods: We analyzed the National Socioeconomic Survey of Access to Health of the EsSalud Insured. Perceived quality of health care was evaluated in ambulatory care, hospitalization and emergency medical services. We reported adjusted ratios of means (RMa) estimated by multiple Poisson regression. Results: Being employed (RMa=0.98; IC95% 0.96-0.99), not knowing the services provided by EsSalud (RMa=0.97; IC95% 0.95-1.00), not receiving information about right to health (RMa=0.95; IC95% 0.93-0.98), perceiving as low the level of accessibility to the health facility (RMa=0.97; IC95% 0.95-0.99) and not feeling comfortable in the health facility of EsSalud (RM=0.92; IC95% 0.91-0.94) were factors associated with lower scores of perceived quality in ambulatory care. In hospitalization, being between 40-59 years old (RMa=0.93; IC95% 0.88-0.97), having a low wealth index (RMa=0.92; IC95% 0.87-0.97), not having received information about right to health (RMa=0.90; IC95% 0.84-0.95) and not feeling comfortable in the health facility of EsSalud (RMa=0.92; IC95% 0.89-0.96) were associated with lower quality score. In emergency, not feeling comfortable in the health facility of EsSalud (RMa=0.89; IC95% 0.93-1.00) was the only factor associated with a lower perceived quality score. Conclusions: We identified factors related to users and service offerings independently associated with perceived quality of care, which can be considered by decision makers for better management of EsSalud.